Breast-feeding counselling mitigates the negative association of domestic violence on exclusive breast-feeding duration in rural Bangladesh. The MINIMat randomized trial. Issue 15 (29th June 2017) - Frith, Amy L; Ziaei, Shirin; Naved, Ruchira Tabassum; Khan, Ashraful Islam; Kabir, Iqbal; Ekström, Eva-Charlotte
Abstract: Objective: To determine if exclusive breast-feeding counselling modifies the association of experience of any lifetime or specific forms of domestic violence (DV) on duration of exclusive breast-feeding (EBF). Design: In the MINIMat trial pregnant women were randomized to receive either usual health messages (UHM) or usual health messages with breast-feeding counselling (BFC) in eight visits. During pregnancy (30 weeks), lifetime experience of any or specific forms of DV was measured. Infant feeding practice information was collected from 0 to 6 months at 15 d intervals. Setting: Matlab, Bangladesh. Subjects: Pregnant and postpartum women ( n 3186) and their infants. Results: Among women in the UHM group, those who had experienced any lifetime DV exclusively breast-fed for a shorter duration than women who did not experience any lifetime DV ( P =0·02). There was no difference, however, in duration of EBF among women in the BFC group based on their experience of any lifetime DV exposure ( P =0·48). Using Cox regression analysis, there was an interaction of exposure to any lifetime DV, sexual violence and controlling behaviour, and counselling group with duration of breast-feeding at or before 6 months ( P -interaction≤0·08). Among the UHM group, experience of any lifetime DV, sexual violence or controlling behaviour was associated with fewer days of EBF ( P <0·05). In contrast, among the BFC group, experience of DV was not associated with duration of EBF. Conclusions: The experience of DV compromises EBF and the support of breast-feeding counselling programmes could assist this vulnerable group towards better infant feeding practices.